Обґрунтування наукових принципів забезпечення якості професійного розвитку персоналу промислового підприємства - Захарова, О.В.; Городничук, Н.В. (Економіка промисловості, 2013)
Обґрунтовано необхідність управління якістю процесу професійного розвитку персоналу промислового підприємства. Визначено фактори, що впливають на якість професійного навчання, та запропоновано їх класифікацію. Досліджено наукові принципи управління якістю професійного розвитку персоналу шляхом проведення аналізу та співставлення принципів реалізації окремих складових даного процесу. Виявлено вплив факторів професійного навчання персоналу та визначено підтримуючі принципи для кожного з підпроцесів. Обоснована необходимость управления качеством процесса профессионального развития персонала промышленного предприятия. Определены факторы, влияющие на качество профессионального обучения и предложена их классификация. Исследованы научные принципы управления качеством профессионального развития персонала путем проведения анализа и сопоставления принципов осуществления отдельных составляющих данного процесса. Выявлено влияние факторов профессионального обучения персонала и определены поддерживающие принципы для каждого из подпроцессов. The necessity of the quality management of the process of professional development of industrial enterprise staff was justified. The factors affecting the quality of training were offered and their classification was defined. The scientific principles of quality management of professional development were investigated by means of the analysis and comparison of the principles of the individual components of the process. The influence of vocational training factors was revealed and supporting principles for each of the subprocesses were determined. The process of quality management of staff development is a complex phenomenon as it consists of two interconnected, but at the same time self-contained subprocesses – quality management and management of professional staff development. Therefore, for the justification of the general principles that should form the basis of an efficient system of quality control of professional staff development it is necessary to consider the interrelated principles for each of two components of this process. In this case, the quality principles of vocational training have to be converted in accordance with the ISO 9001:2008 standard. To determine the justified scientific principles of quality management of staff development it is more advisable to make the analysis and comparison of the principles of individual components of the process. The analysis of current practices of the management of professional staff development allowed us to establish a significant amount of research that emphasize aspects such as training, education, effective teaching, organizing vocational training, etc. The principles based are comprehensive and cover all the aspects of the quality staff development and can be applied at the level of an individual enterprise, industry and economy in whole in the formation of regulatory requirements to the general system of the vocational training. Thus, the implementation of a quality assessment of the effectiveness of professional development is impossible without systematic performance evaluation. This will enable a comprehensive is impossible without systematic performance evaluation. This will enable a comprehensive quantitative and qualitative characteristics both the individual components and the overall effectiveness of the professional development of the staff. The development and continued use of a complex system of indicators to measure the quality of professional development should be the basis for the company expected level of quality and effectiveness of professional development of staff.